what is the equation of the quadratic function that passes through the points (0,-1),(1,0),and (2,-3)
1 answer:
Answer:
-2x^2 + 3x -1
Step-by-step explanation:
y = ax^2 + bx + c
(0,-1):
-1 = a(0)^2 + b(0) + c
-1 = 0 + 0 + c
-1 = c
(1,0):
0 = a(1)^2 + b(1) + c
0 = a + b + c
(2,-3):
-3 = a(2)^2 + b(2) + c
-3 = 4a + 2b + c
Replace c with -1
0 = a + b -1
1 = a + b
-3 = 4a + 2b -1
-2 = 4a + 2b
-1 = 2a + b
Solve:
2a + b = -1
-1a - b = -1
a = -2
2a + b = -1
-2a -2b = -2
-b = -3 divide both by -1: b = 3
a = -2; b = 3; c = -1
y = ax^2 + bx + c or y = -2x^2 +3x -1
You might be interested in
Steven kept 27 paper clips for himself with means 136 paper clips are left. (163-27) now divide 136 by 8 you get 17. Each friend receives 17 paper clips.
The answer is 161.70 N. EXPLANATION To change from mass to weight multiply by gravity (9.8 m/s^2) Fw = m * 9.8 m/s^2 Fw = 16.5 kg * 9.8 m/s^2 = 161.70 N.
Answer:
Step-by-step explanation:
⁷hc8
Answer:
2x + 7= 4x + 17
7=2x+17
-10=2x
-10/2=2x/2
x=−5
Answer:
F
Step-by-step explanation:
Hope this helps